2008
DOI: 10.1007/s10157-007-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term prognosis of blood pressure and kidney disease in women with a past history of preeclampsia

Abstract: Little research has been conducted into the long-term effects of preeclampsia, despite its frequent occurrence. The aim of this review is to examine the association between preeclampsia and the development of hypertension and kidney diseases later in life. To achieve this aim, we evaluated three retrospective studies conducted in our department. In the first study, 52 women who suffered from preeclampsia during their first pregnancy were followed for 2 years after delivery for any long-term effects upon blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 35 publications
2
34
1
4
Order By: Relevance
“…In addition, the same group demonstrated that women were characterized by significantly elevated immunoreactive insulin levels but normoglycemia 17 years after a preeclamptic first pregnancy. 44 Similarly, in our previous study, 45 insulin resistance was apparent in women with a past history of preeclampsia and these findings supported by several studies that insulin resistance and the resultant hyperinsulinemia are causally related to hypertension and renal injury. [46][47][48] A number of potential mechanisms can account for these deleterious effects.…”
Section: Role Of Estrogen In Ckdsupporting
confidence: 84%
“…In addition, the same group demonstrated that women were characterized by significantly elevated immunoreactive insulin levels but normoglycemia 17 years after a preeclamptic first pregnancy. 44 Similarly, in our previous study, 45 insulin resistance was apparent in women with a past history of preeclampsia and these findings supported by several studies that insulin resistance and the resultant hyperinsulinemia are causally related to hypertension and renal injury. [46][47][48] A number of potential mechanisms can account for these deleterious effects.…”
Section: Role Of Estrogen In Ckdsupporting
confidence: 84%
“…There is also a risk of progression towards chronic HPT in one quarter of the cases [9,28]. In fact, it is well known that up to 20% of women with hypertensive pregnancy disorders might persist with high BP levels after 6 weeks postpartum thus develop chronic hypertension [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in fPE women have reported subtle vascular alterations such as arterial stiffness, as measured by pulsewave analysis (PWA) and pulse-wave velocity (PWV) (10,11,25,27,33,37,39,47,57). However, these studies show some inconsistencies; differences in study design, heterogeneity of the preeclamptic phenotype, and the presence or absence of comorbidities (i.e., hypertension and increased BMI) may explain the contradictory findings.…”
Section: This Study Assessed Arterial Stiffness In Healthy Formerly Pmentioning
confidence: 99%
“…The enhanced risk could be the result of preexisting cardiovascular risk factors or longterm effects caused by preeclampsia itself (38,42,52). Since preeclampsia affects the maternal vascular bed, persistent vascular alterations in the postpartum period might potentially contribute to the increased cardiovascular risk of formerly preeclamptic women.Recent studies in fPE women have reported subtle vascular alterations such as arterial stiffness, as measured by pulsewave analysis (PWA) and pulse-wave velocity (PWV) (10,11,25,27,33,37,39,47,57). However, these studies show some inconsistencies; differences in study design, heterogeneity of the preeclamptic phenotype, and the presence or absence of comorbidities (i.e., hypertension and increased BMI) may explain the contradictory findings.…”
mentioning
confidence: 99%